Efektivitas Penerapan Model Attention, Relevance, Confidence, Statisfaction (ARCS) Berbantuan Video Tutorial Untuk Meningkatkan Keaktifan Dan Motivasi Belajar Peserta Didik Di SMK Negeri 1 Sukoharjo - Jonet Ariyanto Nugroho; Sri Wahyuni (Department of Economics Education, Universitas Sebelas Maret, 2018)
The research carried out is Classroom Action Research (Claasroom Action Reseacrh). In general, the purpose of the study was to measure the effectiveness of the application of Attention, Relevance, Confidence, Satisfaction (ARCS) models assisted by video tutorials to improve student loyalty and learning motivation in vocational schools, especially in marketing majors. The specific objectives of this research are: (1) Application of ARCS models in online marketing learning; (2) Making video tutorials for online learning; (3) Testing the effectiveness of ARCS models assisted by video tutorials on the validity and learning motivation of students in vocational schools especially in marketing; (4) Publication of research results in national journals.In this study, an analysis of the focus of the problems studied and design planning for making video tutorials for online marketing learning in vocational high schools and the effectiveness of the application of ARCS) models assisted by video tutorials using qualitative and quantitative approaches by following the implementation path as follows : (1) literature study, to draft the ARCS model and video tutorial; (2) field data collection and data circulation, are carried out to describe the learning and media models currently implemented; (3) Identifying Competency Standards, Online Marketing Syllabus for relevance in the application of ARCS models assisted by video tutorials; (4) Description and analysis of findings and effectiveness of the application of ARCS models assisted by video tutorials.The results showed that the application of ARCS models assisted by video tutorials on online marketing subjects in Vocational Schools was effective in increasing the activeness and learning motivation of students. This was marked by an increase in the students' loyalty to visual activities at 86.11%, oral activities at 83.33%, listening activities at 80.55%, and writing activities at 91.66%. In line with this, the effectiveness of the application of ARCS models with tutorial videos is also able to increase the learning motivation of students from very low criteria of 18.28% to 83.63 which is included in the very high criteria.